Effectiveness of an Educational Program on Nurses’ Knowledge and Practices Concerning Nursing Management of patients’ with Vascular Access in Dialysis Centers at Baghdad Teaching Hospitals - Worood A. Mahmood1 , Khalida M. Khudur2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): The aim of a present study is to determination the effect of an Educational Program on Nurses’ Knowledge and Practices Concerning Nursing Management of patients’ with Vascular Access in Dialysis Centers. Method: A quasi-experimental (two –group pre-post -test) design was conducted at Baghdad teaching hospitals, at 14th October 2018 to 25 December 2019. Non-probability “purposive” sample of (80) staff nurse who have been working at hemodialysis units were selected from Baghdad teaching hospitals which include Al-Yarmook teaching hospital, Baghdad Teaching Hospital, and Al-Kindy Teaching hospital, Al Karama Teaching Hospitals, Imamein-kadhimein Teaching Hospital, Surgical Specialties Hospitals. Nurses were divided into two groups, study groups consist of (40) nurses exposed to the nursing education program, and control group consist of (40) nurses. Results: The results of the study indicated that The majority of staff nurses are female, and they graduated from high school nursing within the age group (23-27) years. The study indicates the nurse knowledge and practices Concerning Nursing Management of patients with Vascular Access in Dialysis was poor level. While posttest results showed that the nurse knowledge and practices was improved to high level which as the positive effect of program.